Tungstophosphoric acid heterogenized onto NH4ZSM5 as an efficient and recyclable catalyst for the photocatalytic degradation of dyes - Leal Marchena, Candelaria (2015)
Materials based on tungstophosphoric acid (TPA) immobilized on NH4ZSM5 zeolite were prepared by wet impregnation of the zeolite matrix with TPA aqueous solutions. Their concentration was varied in order to obtain TPA contents of 5%, 10%, 20%, and 30% w/w in the solid. The materials were characterized by N2 adsorption-desorption isotherms, XRD, FT-IR, 31P MAS-NMR, TGA.-DSC, DRS-UV-Vis, and the acidic behavior was studied by potentiometric titration with n-butylamine. The BET surface area (SBET) decreased when the TPA content was raised as a result of zeolite pore blocking. The X-ray diffraction patterns of the solids modified with TPA only presented the characteristic peaks of NH4ZSM5 zeolites, and an additional set of peaks assigned to the presence of (NH4)3PW12O40. According to the Fourier transform infrared and 31P magic angle spinning-nuclear magnetic resonance spectra, the main species present in the samples was the [PW12O40]3- anion, which was partially transformed into the [P2W21O71]6- anion during the synthesis and drying steps. The thermal stability of the NH4ZSM5TPA materials was similar to that of their parent zeolites. Moreover, the samples with the highest TPA content exhibited band gap energy values similar to those reported for TiO2. The immobilization of TPA on NH4ZSM5 zeolite allowed the obtention of catalysts with high photocatalytic activity in the degradation of methyl orange dye (MO) in water, at 25 °C. These can be reused at least three times without any significant decrease in degree of degradation.